2021
DOI: 10.1016/j.hsr.2021.100002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of antidepressant prescribing in adults with comorbid depression and type 2 diabetes mellitus: A systematic review and meta-analysis

Abstract: Highlights Antidepressant gender disparity less in type 2 diabetes than general population No evidence of ethnic disparity in antidepressant prescribing in type 2 diabetes No evidence of disparity in antidepressant prescribing for insulin users Considerable evidence gaps for antidepressant prescribing in type 2 diabetes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A recent systematic review of antidepressant use in type 2 diabetes highlighted a dearth of studies on the use of antidepressant medication in people with type 2 diabetes, with only seven included studies, of which six were in the USA and one in Australia 28 . The prevalence of antidepressant use in the populations studied in the USA varied from 18% to 87% and in Australia it was 37%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of antidepressant use in type 2 diabetes highlighted a dearth of studies on the use of antidepressant medication in people with type 2 diabetes, with only seven included studies, of which six were in the USA and one in Australia 28 . The prevalence of antidepressant use in the populations studied in the USA varied from 18% to 87% and in Australia it was 37%.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of antidepressant use in type 2 diabetes highlighted a dearth of studies on the use of antidepressant medication in people with type 2 diabetes, with only seven included studies, of which six were in the USA and one in Australia. 28 this may reflect the fact that antidepressant medication can be used for other common mental health problems like anxiety, and the presence of higher rates of antidepressant medication prescribing in the United Kingdom. 32,33 The risk factors identified for depression in people with type 2 diabetes by Lunghi et al 29 were similar to this study.…”
Section: Comparability With Other Findingsmentioning
confidence: 99%
“…Untreated depression results in harmful decision-making and risky behaviors, such as smoking, stagnation, and unhealthy food consumption, causing unhealthy weight gain-all life choices that exacerbate depression. [9] Depression decreases functionality, diminishes task accomplishment, and hinders communication skills, thereby generating a more complex process of diabetes management. Typically, the medical community identifies feeling down or blue when referring to "clinical depression"; however, it is complicated for healthcare providers to decipher the differences between clinical depression and emotional reactions to stressful situations as each response differs.…”
Section: Depression Versus Distressmentioning
confidence: 99%
“…The main remedial aim in treating diabetes comorbid with depression is to reduce depressive symptoms and improve hyperglycemia using antidepressants and hypoglycemic interventions 33–35 . However, a study reported the moderate effect of antidepressants used during diabetes 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The main remedial aim in treating diabetes comorbid with depression is to reduce depressive symptoms and improve hyperglycemia using antidepressants and hypoglycemic interventions. [33][34][35] However, a study reported the moderate effect of antidepressants used during diabetes. 36 Already-approved antidepressant drugs exhibited major cardiometabolic effects; citalopram and mirtazapine were found to induce appetite, resulting in weight gain, which further elevates hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%